SENGKETA PEMUNGUTAN PAJAK PERTAMBAHAN NILAI SEBAGAIDAMPAK PERBEDAAN PERSEPSI DALAM INTERPRETASI KRITERIA PENGUSAHA KENA PAJAK TERTENTU - Purwanto, Thesa Adi; Wulan, Retno (UI Scholars Hub, 2019)
In carrying out the obligation to collect Value Added Tax (PPN), Taxpayers who carry out the business of selling used motor vehicles must first be designated as Taxable Entrepreneurs (PKP) by the provisions concerning entrepreneurs conducting certain business activities. Actually, this matter has been explained in the Minister of Finance Regulation Number 79 / PMK.03 / 2010 concerning Guidelines for Calculation of Input Tax Crediting for Taxable Entrepreneurs Who Perform Certain Business Activities, but in practice there are still many differences in perceptions between tax officers and Taxpayers in determining PKP category that can implement the input tax crediting guidelines. This study aims to describe differences in perceptions between tax officers and taxpayers who can lead to tax disputes accompanied by case examples. In this study, the approach used is a qualitative approach, with a type of descriptive research. Based on the case examples taken in the study, it can be concluded that differences in perceptions between tax officers and taxpayers occur because there are only phrases in the criteria for certain business activities contained in the regulations of the finance minister. The results of the study indicate that the Directorate General of Taxes has not provided clear criteria for business activities in the field of sale and purchase of used motor vehicles.